2022
DOI: 10.3390/ijerph191912980
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of Low Air Quality-Related Health Impacts among Socioeconomic Groups in the World of Work

Abstract: This research aimed to assess the perceptions of air quality and health symptoms caused by low urban air quality among vulnerable socio-economic groups in the world of work in Bangkok, Thailand through a questionnaire survey of 400 workers of both formal and informal sectors in the five districts with different socio-economic characteristics and levels of air pollution. The findings showed symmetry between air quality-monitoring data and health symptoms of different socio-economic groups but asymmetry between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Higher SES is linked to better mental health, as seen by the negative correlation (r = -0.282), which suggests that economic disparities have a significant influence on the mental health of underprivileged urban areas. These results highlight how crucial it is to implement focused interventions to address the financial factors that influence mental health in vulnerable people, related to research by [2], [22]- [25].…”
Section: Discussionmentioning
confidence: 95%
“…Higher SES is linked to better mental health, as seen by the negative correlation (r = -0.282), which suggests that economic disparities have a significant influence on the mental health of underprivileged urban areas. These results highlight how crucial it is to implement focused interventions to address the financial factors that influence mental health in vulnerable people, related to research by [2], [22]- [25].…”
Section: Discussionmentioning
confidence: 95%
“…It suggested that the mutant variants appear to be more closely associated with air pollutants than the original strain [30]. Bangkok, Thailand a study found that people working near the streets, highways, and industrial zones tended to have more health symptoms related to low air quality, and informal sector workers faced more health risks than formal sector workers [31].…”
Section: Case Studies On Air Quality and Healthmentioning
confidence: 99%